WHO’S CAPTURING THE GREEN VALUE IN KUALA LUMPUR’S OFFICE RENTAL SPACES? - Mashitoh Halim; Noraliza Basrah; Rohayu Abdul Majid; Noorhalil Ismail (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2024)
This study aims to understanding the dynamics within the green office rental market in Kuala Lumpur by identifying the industries that capture the most value from green office spaces and analyzing tenant preferences in this evolving landscape. The primary objective is to uncover the current nature of businesses occupying green office spaces and their preferences regarding location, building features, certification levels, and green attributes. By employing a quantitative methodology, the research commenced with an extensive literature review to situate the study within the broader context of existing academic work. Primary data was meticulously collected from GreenBuildingIndex Sdn. Bhd. (GBI) and the Valuation and Property Services Department (JPPH), incorporating sample data from 50 green office buildings documented by GBI and 2,707 rental office spaces recorded by JPPH. The analysis utilized the Statistical Package for the Social Sciences (SPSS) to integrate and examine the data collected from these distinct sources. Furthermore, the nature of businesses occupying these green spaces was ascertained through comprehensive verification using company websites and professional platforms. The findings reveal a notable preference among tenants from sectors prioritizing sustainability, innovation, and strategic positioning, such as Energy and Technology, Financial Services, ICT, and Management Services. These sectors demonstrate an acute awareness and commitment to environmental sustainability, opting for green office spaces that align with their corporate ethos of innovation and responsibility. Moreover, the study delineates tenant preferences in selecting green office spaces, highlighting a clear inclination towards buildings that not only offer prestigious locations and advanced green features but also possess recognized green certifications, indicating a mature and discerning tenant base within the market. In conclusion, the research provides insightful revelations about the commercial dynamics of Kuala Lumpur’s green office rental market, showcasing a significant shift towards sustainability across diverse sectors. The preferences regarding location, certification, and building attributes reflect a complex interplay of economic, environmental, and social factors, driving the demand for green office spaces in Kuala Lumpur. This study contributes to the understanding of how businesses are aligning with sustainability trends, offering a valuable perspective on the green value captured in the office rental market of Kuala Lumpur.